The value added tax: The impact of procedures applyed to agricultural producers (reverse charge, quota reducing and the exemption from vat) - Mircea Toma (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
The introduction or elimination, increase or decrease of taxes and contributions, theoretical and practical, can not ignore the direct and / or underlying effects (collateral) on chain: Financial institutions, Suppliers of inputs, Agricultural producers, En-gross traders, Processing industry, En-detail traders, Consumer, State Budget. Solutions require transparency, solidarity, equity, social justice in the distribution of efforts and usufruct (profit) for the whole chain participants in achieving useful goods and services to human society. A particularly aspect has VAT with effect from 1 July 1993, as a Romanian fiscal system compatible with EU procedures. By the additions and changes to VAT management procedures for agricultural activities (exemption from VAT of individual producers, the reverse charge in the production of cereals and technical crops, reducing the quota of VAT collected on chain at 9% for bread), fiscal inequity was created between farmers according to the legal status of the organization and operation, between sectors of agricultural production, but also to the users of agricultural production. The most disadvantaged are those of 3,859,000 individual farmers, family farms and associations without legal status, that use 7.45 million ha (56% of the total utilized agricultural of 13,306,000 ha).
Keywords: 330; VAT; reverse charge; exemption; reduced VAT rate; VAT collection; tax evasion; farms; farmers; financial resources; efficiency; economic crisis; budget revenues